2016
DOI: 10.1007/s10342-016-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Increases in volatile organic compound emissions of Scots pine in response to elevated ozone and warming are modified by herbivory and soil nitrogen availability

Abstract: Climate change in the boreal forests include, e.g., warming, increased tropospheric ozone concentration, higher nitrogen (N) deposition and increased risk of insect outbreaks. Climate change influences emissions of biogenic volatile organic compounds (BVOCs) affecting plant defense, communication and atmospheric feedbacks. We studied the effects of elevated temperature (ca. 1°C), elevated ozone (ca. 1.5 9 ambient), two soil N availability levels (prevailing and 120 kg N ha -1 a -1 ) and herbivory on BVOC emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 60 publications
4
52
0
Order By: Relevance
“…Leaf injury has been reported to activate the phenylalanine (PAL) pathway, eventually releasing high amounts of tannins, total phenolics and increasing antioxidative capacity (Kerchev et al, 2012). This confirms that changes in multiple environmental factors may interact with plants, potentially resulting in additive (Carriero et al, 2016), synergistic (Zhang et al, 2009) or antagonistic (Kivimäenpää, Ghimire, Sutinen, HaIkio, Kasurinen, & Holopainen, 2016) effects on plants and insects.…”
Section: Stability Performance Of the Genotypes Environmental Factorsupporting
confidence: 51%
“…Leaf injury has been reported to activate the phenylalanine (PAL) pathway, eventually releasing high amounts of tannins, total phenolics and increasing antioxidative capacity (Kerchev et al, 2012). This confirms that changes in multiple environmental factors may interact with plants, potentially resulting in additive (Carriero et al, 2016), synergistic (Zhang et al, 2009) or antagonistic (Kivimäenpää, Ghimire, Sutinen, HaIkio, Kasurinen, & Holopainen, 2016) effects on plants and insects.…”
Section: Stability Performance Of the Genotypes Environmental Factorsupporting
confidence: 51%
“…Shoot biomass of Scots pine will increase in a warmer climate (Rasheed et al 2017), and thus the amount of litter and forest floor BVOC emissions will increase. Moreover, warming increases BVOC emissions from pine foliage (Kivimäenpää et al 2016). Therefore, BVOC emission rates are expected to increase at the forest level.…”
Section: Discussionmentioning
confidence: 99%
“…Warming affects also the BVOC composition. For example, Kivimäenpää et al (2016) showed that 3-carene emissions from Scots pine shoots were not affected by long-term warming, while α-pinene emissions were increased by a factor of 1.5-2. Such changes, as well as Scots pine chemotypes, can affect oxidative properties of the atmosphere under climate change because α-pinene is more reactive.…”
Section: Discussionmentioning
confidence: 99%
“…Hot, dry summers can modify tree defenses and resistance to herbivory. Elevated temperature and ozone can increase the emission of volatile organic compounds and modify herbivory [84]. Temperate insects are generally cold tolerant and exhibit adaptations such as diapause and super-cooling tolerance that can facilitate shifts to northern latitudes or higher elevations even with a slight increase in temperature [85].…”
Section: Insect Abundancementioning
confidence: 99%